Equilibrium Adsorption Studies of Methylene Blue onto Blended Agricultural Wastes-Based Activated Carbon - Nuhu, A. A.; Omali , I.C.P; Clifford, C. O. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
An effective adsorbent was prepared from Caesalpinia Pulcherrima and Melaleuca Leucadendron (Cajuput tree capsule) husk (BAC-PA) by Phosphoric acid activation method and its adsorption characteristic was studied for the removal of methylene blue from aqueous solution. Batch mode adsorption experiments were adopted. Maximum dye removal capacity was observed at a pH of 9. Equilibrium data were obtained at 303, 313, 323, 333 and 343K for the initial concentrations of 20, 40, 60, 80 and 100 mg/L. Adsorption isotherm models such as Langmuir, Freundlich, Temkin and Dubinin – Radus-Kevich isotherms were used to correlate the equilibrium data. Parameters obtained from the isotherm models were discussed in detail. This study will help in giving supporting evidence on the effective use of blended activated carbon from agricultural waste precursors in the adsorption of methylene blue.